Metodologia de gerência de riscos na operação e manutenção de transformadores de potência - Jeferson Inacio Lopes (2010)
The objective of this master thesis is to present a Risk Management Methodology applied to Power System Transformers, related to Operation, Maintenance and Monitoring tasks. It is an innovative methodology that applies techniques for risk evaluation on transformers monitoring and control. The basic philosophy that underlies the method is the conception of a called Power Transformers Critical Matrix. It takes into consideration different aspects, such as the equipment failure frequency expectation and the possible impacts related to financial (time and cost), operational, health, security and environmental consequences. It also defines a Transformers Risk Answer Matrix focused on monitoring and control proposition. The way the methodology is idealized permits the engineering staff to contribute and take decisions related to operation, maintenance and planning activities, to improve and adjust already proposed parameters, as well as to intensify statistical studies. Significant gain is expected from the use of the methodology on transformers management. In order to emphasize such benefits, this work presents the results of the methodology applied to a group of 20 real transformers. Actions proposed to improve their operation and maintenance are detailed. With the application of these proposals, reductions of transformers risks and failures are expected. Technical and financial management is also projected, mainly regarding the prioritization for maintenance, repair and transformers monitoring investment